KONSEP DAN IMPLEMENTASI KEPEMIMPINAN DALAM PENDIDIKAN UNTUK MEWUJUDKAN KUALITAS PENDIDIKAN - Amara Mayasena; Mulyadi; Aulia Putri; Elviana Fadilah; Amelia (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
Educational leadership plays an important role in improving the quality of education in educational institutions. Educational leaders, especially school principals, are not only responsible for administrative management but also for directing, influencing, and mobilizing all members of the school community to achieve educational goals effectively and efficiently. This article aims to examine the basic concepts of leadership, the characteristics of effective educational leadership, and the implementation of leadership in education to realize educational quality. The method used in this article is a literature review, which involves analyzing various scientific journals, reference books, and other relevant academic sources related to educational leadership. The literature review was conducted to gain a comprehensive understanding of concepts, theories, and findings from previous studies concerning leadership in educational settings. The results of the review indicate that effective educational leadership is characterized by clear vision and mission, the ability to empower teachers and educational staff, effective communication, and the capacity to manage change wisely. Proper leadership implementation can create a conducive learning environment, improve teacher performance, and support the achievement of higher educational quality. Therefore, effective educational leadership is one of the key factors in realizing sustainable educational quality.